Herodotean Ironies - Rutherford, Richard (Histos, 2018)
‘Irony/ironic’ are terms frequently used in discussion of Herodotus, whether applied to particular passages or to the text as a whole. This paper aims to distinguish different types of irony which have been or can be detected in the text of the Histories, and to map these on a spectrum ranging from those which are clearly indicated by the narrator to those which demand more by way of interpretation and supplement from the reader. Types described and illustrated include dramatic, oracular, historical, cross-cultural and situational ironies; but the idea that the entire work is in some sense ironic is rejected. Irony as a tool of interpretation seems indispensable, but needs to be handled with circumspection and self-conscious care. The paper ends with some suggestions for further explorations of the topic. Endnotes provide further documentation, principally on ironies of the oracular type.